2014
DOI: 10.1371/journal.pone.0099007
|View full text |Cite
|
Sign up to set email alerts
|

Does Exposure to a Radiofrequency Electromagnetic Field Modify Thermal Preference in Juvenile Rats?

Abstract: Some studies have shown that people living near a mobile phone base station may report sleep disturbances and discomfort. Using a rat model, we have previously shown that chronic exposure to a low-intensity radiofrequency electromagnetic field (RF-EMF) was associated with paradoxical sleep (PS) fragmentation and greater vasomotor tone in the tail. Here, we sought to establish whether sleep disturbances might result from the disturbance of thermoregulatory processes by a RF-EMF. We recorded thermal preference a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A whole-body exposure system was designed inside a climatic chamber for in vivo experiments to 900 MHz CW radiation. A detailed description of the RF exposure system has previously been published 4 . Briefly, a 900 MHz signal was generated from a radiofrequency power source type RFS7001800-6×0.5 (RFPA, Artigues-près-Bordeaux, France), located outside the climatic chambers and connected to a four-output divider which simultaneously supplied four antennas Kathrein 800-10465 (Rosenheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A whole-body exposure system was designed inside a climatic chamber for in vivo experiments to 900 MHz CW radiation. A detailed description of the RF exposure system has previously been published 4 . Briefly, a 900 MHz signal was generated from a radiofrequency power source type RFS7001800-6×0.5 (RFPA, Artigues-près-Bordeaux, France), located outside the climatic chambers and connected to a four-output divider which simultaneously supplied four antennas Kathrein 800-10465 (Rosenheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The obtained results suggested that the exposure caused increased constriction of blood vessels, and increased food intake, but without any effects on sleep pattern. In the second study from the same group (Pelletier et al 2014), the same rat model and exposure conditions were used for thermal preference and sleep stage distribution studies. Exposed animals shifted their thermal preference after the exposure period towards higher temperatures.…”
Section: Other Effectsmentioning
confidence: 99%
“…Mechanistically, one may hypothesize that local skin thermal sensitivity was modulated in relationship to whole-body thermal states [ 32 ]. Indeed, RF-EMF exposures were previously shown to modify thermal perception or to increase whole temperature in rodents [ 33 , 34 ]. In addition, one may hypothesize that local skin thermal sensitivity was modulated through the chemical mediators influencing the higher-order midbrain regions controlling pain perception.…”
Section: Discussionmentioning
confidence: 99%